2002
DOI: 10.1177/074873040201700402
|View full text |Cite
|
Sign up to set email alerts
|

The "Other" Circadian System: Food as a Zeitgeber

Abstract: It is not surprising that limiting food access to a particular time of day has profound effects on the behavior and physiology of animals. It has been clear for some time that pre-meal behavioral activation, a rise in core temperature, elevated serum corticosterone, and an increase in duodenal disaccharidases are under circadian control and that the observed circadian properties are not abolished by lesions of the suprachiasmatic nucleus (SCN), but the search for the locus of a separate food-entrainable oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
195
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(202 citation statements)
references
References 68 publications
4
195
0
3
Order By: Relevance
“…The timing of food intake is an important entrainment signal for peripheral clocks, best characterized in, but not limited to, the liver and adipose clocks (Stephan 2002). Anticipatory behavior just before scheduled feeding (food anticipatory activity (FAA)) is seen in animals with restricted access to food.…”
Section: Ghrelin and Insulinmentioning
confidence: 99%
“…The timing of food intake is an important entrainment signal for peripheral clocks, best characterized in, but not limited to, the liver and adipose clocks (Stephan 2002). Anticipatory behavior just before scheduled feeding (food anticipatory activity (FAA)) is seen in animals with restricted access to food.…”
Section: Ghrelin and Insulinmentioning
confidence: 99%
“…In normal animals, light-driven diurnal behaviour can be easily overcome by alterations in energy supply, such as during restricted feeding schedules (RFS) (Mistlberger 1994;Stephan 2002). During RFS, food is only available to animals during set periods that typically occur outside of their normal feeding period (such as during the day for nocturnal rodents).…”
Section: An Anatomically Distinct Food-entrainable Oscillatormentioning
confidence: 99%
“…Under RFS numerous physiological and metabolic functions become entrained to the availability of food, e.g., locomotor activity, body temperature, insulin and corticosterone release. Strong support for the existence of a foodentrainable timing system is the circadian pattern of food anticipatory activity (FAA) rhythms that emerge in intact and SCN-ablated animals maintained on RFS (Krieger 1972;Stephan and Zucker 1972;Boulos and Terman 1980;Mistlberger 1994;Stephan 2002). Further, feeding-related anticipation is not dictated simply by a threshold of energy depletion, as such behaviours are not observed in fasted animals with no prior RFS conditioning, nor during the first few days of RFS.…”
Section: An Anatomically Distinct Food-entrainable Oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…When subjected to scheduled-feeding, most animals display an increase in locomotor activity in anticipation of the forthcoming meal, and this can occur several hours before mealtime. This is known as food anticipatory activity (FAA) (Mistlberger 1994) and has been reported in a wide variety of animals, from bees to mammals (Stephan 2002) and also in fish López-Olmeda and Sánchez-Vázquez 2010). To the authors knowledge, the first evidence of FAA in fish was observed in the bluegill (Lepomis macrochirus) and largemouth bass (Micropterus salmoides), which displayed pre-feeding activity consisting of increases in swimming activity 1-3 h before the scheduled mealtime (Davis 1963).…”
mentioning
confidence: 96%